Development of the Project of Women's Collection of National Style (Eurasian Journal of Engineering and Technology, 2024)
In the direction of "women's national clothing" for production enterprises, bringing new things to the world of fashion, which is developing rapidly even with the time, which is perfect in terms of quality, comfortable, hygienic and harmless appearance